2002
DOI: 10.1037/0735-7028.33.5.490
|View full text |Cite
|
Sign up to set email alerts
|

The stalking of psychologists by their clients.

Abstract: A number of practicing psychologists have become victims of threats and/or harassment from clients. This preliminary study provides descriptive information for a group of psychologists and their experiences with clients who have stalked them. Results revealed that (a) there is no specific profile for the psychologists who had been stalked; (b) the stalked psychologists subsequently employed significantly more safety measures than those who had not; and (c) the clients who stalked were usually single, likely ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 11 publications
4
50
0
Order By: Relevance
“…Lifetime prevalence rates found in this study were higher than that found in the general population, but conform to high rates among other mental health professionals (Galeazzi et al, 2005;Purcell, Powell & Mullen, 2005;Ashmore et al, 2006). Our fi ndings confi rm previous reports that the risk of male healthcare workers appears greater than that observed in the general population (Gentile et al, 2002;Galeazzi et al, 2005), but there were no overall gender differences in those stalked. Unlike other studies (Purcell, Powell & Mullen, 2005;Galeazzi et al, 2006), no speciality was found to be at higher risk, but numbers were probably too small for signifi cance to emerge.…”
Section: Discussionsupporting
confidence: 89%
“…Lifetime prevalence rates found in this study were higher than that found in the general population, but conform to high rates among other mental health professionals (Galeazzi et al, 2005;Purcell, Powell & Mullen, 2005;Ashmore et al, 2006). Our fi ndings confi rm previous reports that the risk of male healthcare workers appears greater than that observed in the general population (Gentile et al, 2002;Galeazzi et al, 2005), but there were no overall gender differences in those stalked. Unlike other studies (Purcell, Powell & Mullen, 2005;Galeazzi et al, 2006), no speciality was found to be at higher risk, but numbers were probably too small for signifi cance to emerge.…”
Section: Discussionsupporting
confidence: 89%
“…As with previous studies (e.g. Meloy and Gothard, 1995;Harmon et al, 1995Harmon et al, , 1998Mullen et al, 1999;Gentile, 2001;Rosenfeld and Harmon, 2002;Meloy and Boyd, 2003) both Axis I and II mental disorders were confi rmed. In so far as the diagnostic data differ from previous work, it is in the frequency with which psychosis was identifi ed.…”
Section: Discussionsupporting
confidence: 54%
“…In studies of perceived motivation for stalking of professionals in other mental health disciplines, 42% of psychologists Purcell et al (2005), 21% of therapists (Hudson-Allez 2002), and 34.1% of psychiatrists (McIvor et al 2008) who reported being stalked, believed that the client was angry either because of negative outcomes of an assessment, or the termination of treatment. Stalking behavior of mental health professionals motivated by resentment or retaliation is most commonly perpetrated by males who have never been married, misuse substances, have a diagnosis of personality disorder or major mental illness, have a history of assault and self-harm, and have repeated hospitalizations (Galeazzi et al 2005;Gentile et al 2002;McIvor et al 2008;Rosenfeld and Harmon 2002;Sandberg et al 1998Sandberg et al , 2002.…”
Section: Typologies Of Stalkingmentioning
confidence: 99%